2022
DOI: 10.1002/jmd2.12315
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum of early onset “Mediterranean” (homozygous p.P131L mutation) mitochondrial neurogastrointestinal encephalomyopathy

Abstract: Mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) is an autosomal recessive mitochondrial disorder characterized by cumulative and progressive gastrointestinal and neurological findings. This retrospective observational study, aimed to explore the time of presentation, diagnosis and clinical follow‐up of 13 patients with a confirmed MNGIE disease of Mediterranean origin. The mean age of symptom onset was 7 years (6 months−21 years) and the average diagnosis age was 15.4 years ±8.4. Four of 13 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Three patients of these patients had a homozygous p.P131L (c.392C>T) TYMP mutation, and one patient had a homozygous p.G72E (c.215G>A) mutation. We concluded that the “Mediterranean”/homozygous p.P131L (c.392C>T) mutation is associated with a rapidly progressive clinical course and poor prognosis 12 . The mean age at diagnosis of our patients was 16.4 years and all patients had persistent GI manifestations and neurological deficit findings at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Three patients of these patients had a homozygous p.P131L (c.392C>T) TYMP mutation, and one patient had a homozygous p.G72E (c.215G>A) mutation. We concluded that the “Mediterranean”/homozygous p.P131L (c.392C>T) mutation is associated with a rapidly progressive clinical course and poor prognosis 12 . The mean age at diagnosis of our patients was 16.4 years and all patients had persistent GI manifestations and neurological deficit findings at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 69%
“…In the study published by Kalkan Uçar et al. in 2022, patients diagnosed with MNGIE at Ege University Faculty of Medicine, Department of Pediatrics, Department of Pediatric Metabolism and Nutrition were evaluated 12 . In this patient group, we performed AHSCT on four patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) is a rare autosomal recessive multisystem disorder characterized by severe gastrointestinal and neurological symptoms (Kalkan Uçar et al, 2022; Pacitti et al, 2018). Gastrointestinal dysmotility, cachexia, peripheral neuropathy, diffuse leukoencephalopathy, external ophthalmoplegia, and ptosis are the main manifestations (Hirano et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal dysmotility, cachexia, peripheral neuropathy, diffuse leukoencephalopathy, external ophthalmoplegia, and ptosis are the main manifestations (Hirano et al, 2021). TYMP gene is identified as the pathogenic gene (Kalkan Uçar et al, 2022). It encodes thymidine phosphorylase that catalyzes the reversible phosphorylation of thymidine and deoxyuridine to thymine, uracil, and 2-deoxyribose 1-phosphate (Valentino et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation